DEMAM BERDARAH DENGUE DI DESA GONDANG TANI WILAYAH KERJA PUSKESMAS GONDANG KABUPATEN SRAGEN - heraswati, Diah nia; wati, Yuli Kusuma (MOTORIK Jurnal Ilmu Kesehatan (Journal of Health Science), 2011)
FACTORS THAT IN CONNECTION WITH FAMILY LEADER ACTION IN MEANS PREVENTION DISEASE DANGUE REGIONAL COUNTRYSIDE GONDANG TANI WORK GONDANG CENTER SOCIETY HEALTY SRAGEN REGENCY   ABSTRACT   Countryside of gondang tani is inclusive of area of endemis DBD, sum up the patient of  DBD years 2006 as much 15 case, year 2007 as much 42 case or twice the a lot of compared to year 2006 by IR above 2 per 10.000 resident (2,46%). This research aim to know the relation of between educations, sum up the family member, information DBD, social participation, and ill experience with the action of family head move the family member in prevention of disease DBD. This research represent the research observational with the apporoach of cross sectional study. Population in this research is all family head (KK) residing and noted as resident in countryside of gondang tani of sragen regency amounting to 435 KK with the  amount sampel as much 105 family head taken by simple random sampling. Analyzes data test of chi square with computer pachet of SPSS. Result of research indicated that there are relation of between education (p 0,000), amount of family member (p value = 0,000), information DBD (p 0,002),social participation (p  0,000) and ill experience (p 0,000)  with family leader in prevention disease dangue. Keyword: Action, Family Leader, Preventative, DBD   Conclusion : The findings from this research a strong relationship was observed brtween lung cancer of age p:0,009 (p<0,05), smoking p:0,003, passive smoking p : 0,001 and low consumption of fruit and vegetable p=0,005. Keyword : Lung cancer, smoking, exposures, diet, family history